ANALYSIS OF ONE-WAY TRAFFIC REGULATION IN THE MAJALENGKA SQUARE AREA - Rini Nurhasanah; Mulia Pamadi (LEADER: Civil Engineering and Architecture Journal, 2024)
A one-way traffic control system is a traffic system that converts a two-way road into a one-way road. This system aims to increase safety, road, and intersection capacity. This can improve the smoothness of traffic, which is usually applied in urban areas. Majalengka also implements a one-way road traffic system in several areas, such as the Majalengka Square area. This research aims to determine the system for regulating one-way road traffic so that drivers have the awareness to obey traffic rules without violating one-way road traffic. The case study in this research is located on Jalan One, Alun-Alun Majalengka Area, Jl. Ahmad Yani, Majalengka Kulon, Kab. Majalengka, Majalengka Regency, West Java. The data used in this research is primary data obtained directly through observation, personal interviews, or experimental results. The traffic volume on Jalan Ahmad Yani Majalengka Kulon is measured by counting the number of vehicles passing at the observation point. The survey was carried out directly at the research location for two days, namely Tuesday and Sunday, with a period of 1 hour divided by 15 minutes. Each period is held in the morning from 06.30-07.30, in the afternoon from 12.00-13.00, and in the afternoon (16.00-17.00). The survey results are in the form of a manual grouping of each type of vehicle. Therefore, data collection and calculations are required to determine the volume and side resistance on a road. After data collection and calculations have been carried out, it can be concluded that the volume of traffic flow in the Majalengka Square area is quite dense in the morning, and the side obstacle class in the afternoon is medium class.